SATIRE OR HATE SPEECH: AN EXAMPLE OF CARICATURES BY PREDRAG KORAKSIĆ CORAX DEDICATED TO THE SERBIAN ORTHODOX CHURCH - Jovićević, Marina (National interest, 2023)
The aim of the work is to analyze a total of 96 caricatures by the author Predrag Koraksić Corax. All of them are dedicated to the Serbian Orthodox Church, in the context of the messages that the author would like to send and the reactions of the recipients. In the paper are analyzed the terms of satire and caricature, freedom of speech and expression and hate speech. The importance of the mass media and their role in spreading information is outlined as well. The purpose of caricature as a form of satire is to point out unacceptable forms of behavior and to act as a social corrector. The role of the satirical form in which such messages are transmitted is highlighted, and that is why it is very difficult to respond to it. Besides, we have taken into consideration the broad scope and continuity of dealing with the topic of the relation of Serbian Orthodox Church officials to various social phenomena in a critical and personal way of the author of caricatures. It is concluded that it is impossible to draw a clear conclusion as to whether the tiny border between freedom of speech and hate speech has been crossed. It is fluid and very difficult to determine. However, in certain cases, when the bishops of the Serbian Orthodox Church are depicted as devils or as persons of marked immorality, it can be concluded that the author goes beyond the scope of freedom of speech and enters into the scope of hate speech. This is offending not only for the clergy but it also hurts the religious feelings of the believers of the Serbian Orthodox Church.